Kebijakan Dividen di Indonesia: Bukti dari Perusahaan Manufaktur - Rahayu, Ruwita Try; Meidiaswati, Harlina (Jurnal Ilmu Manajemen, 2024)
This research attempts to identify the factors affecting dividend policy decision. The independent variables of this research are corporate governance (proxied by audit quality and board independence), investment opportunities, collateralizable assets, and company life cycle. Also previous years dividend and profitability as control variables. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018-2022. The sample was selected using purposive sampling methods and 62 sample companies that met the criterias were obtained. The data was analyzed using logistic regression analysis technique. This findings of this research confirm that company life cycle has a positive and significant effect on dividend policy. As companies reach the maturity stage, the propensity to pay dividends increases. Meanwhile, corporate governance, investment opportunities, and collateralizable assets do not affect dividend policy of manufacturing companies. Furthermore, the control variables previous years  dividend and profitability have a positive and significant effect on dividend policy of manufacturing companies.